KONTRA PERSEPSI ASAS KEBEBASAN BERKONTRAK DALAM UU NO 2 TAHUN 1960 TENTANG BAGI HASIL PERTANIAN DENGAN SISTEM IJON (Penyuluhan Hukum Pada Masyarakat di Desa Kaidundu Kecamatan Bulawa Kabupaten Boen Bolango Provinsi Gorontalo) - Dolot Alhasni Bakung; Sri Nanang Meiske Kamba; Mohamad Hidayat Muhtar; Zamroni Abdussamad; Julius T. Mandjo (Jurnal Nusantara Berbakti, 2023)
The implementation of the ijon system by the community, especially farmers, has become a habit that has been passed down from generation to generation and has become entrenched in a number of areas, including Gorontalo. The 1945 Constitution, especially in Article 18B paragraph two (2) which reads that the State recognizes and respects customary law community units along with their traditional rights as long as they are still alive and in accordance with the development of society and the principles of the Unitary State of the Republic of Indonesia, which is regulated in law. Even so, buying and selling under the debt bondage system, in the eyes of the law, is strictly prohibited because in buying and selling the bonded bond system is very unclear because this is a form of extortion that can harm other people. The sale and purchase of the ijon system has also been confirmed in article 8 paragraph 3 of Law number 2 of 1960 concerning production sharing agreements, which reads: "payments by anyone, including owners and cultivators, to cultivators or owners in whatever form they have elements of ijon, are prohibited". The provisions used as the legal basis for the use of standard contracts in Indonesia are Article 1338 Paragraph (1) of the Civil Code which stipulates: "all agreements made legally apply as laws for those who make them" from the words all can be interpreted that every legal subject can make an agreement with any content, there is freedom of the legal subject to determine the form of the agreement. In other words, through the principle of freedom of contract, legal subjects have the freedom to make agreements, including opening opportunities for legal subjects to make new agreements that have not been regulated in the Civil Code so that they can follow the needs of society due to the times